2015
DOI: 10.5152/jtgga.2015.15045
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of DaVinci Robot in uterine transplantation

Abstract: The first human uterine transplantation was attempted in Saudi Arabia in 2002. However, necrosis of the graft occurred 99 days after surgery; thus, the attempt failed (1) that was followed by a lot of criticism. The second case was a 21-year-old patient with Mayer-Rokitansky-Kuster-Hauser syndrome in Turkey who achieved normal cycles and an implanted embryo post transplantation (2). Moreover, recently nine women in Sweden successfully received a transplanted uterus (3). The 6-month results of the first clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Robotic surgery has become a common technique for gynecological surgeons during the past decade (21,22). Some of the advantages of robotic surgery are a three-dimensional high-definition view, efficient microsuturing through laparoscopic ports, wristed instruments with seven degrees of freedom for improved dexterity, infiltration of a surgeon's natural tremor, and less operator fatigue (23)(24)(25). We have performed >1,000 robotic radical hysterectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic surgery has become a common technique for gynecological surgeons during the past decade (21,22). Some of the advantages of robotic surgery are a three-dimensional high-definition view, efficient microsuturing through laparoscopic ports, wristed instruments with seven degrees of freedom for improved dexterity, infiltration of a surgeon's natural tremor, and less operator fatigue (23)(24)(25). We have performed >1,000 robotic radical hysterectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the first human uterus transplant using laparotomy or laparoscopy or robot is also based on the status of surgery and medical technology in each unit. 25 Spanish and Japanese teams favoring the Swedish LD model, whereas teams in Turkey, Italy, France, Belgium and the UK prefer using the DD. 26 As summarized in Table 1, living donors have to face the risk of hysterectomy for uterus retrieval, including massive bleeding, ureterovaginal fistula, ureter laceration, bladder hypotonia and ovarian dysfunction et al But an observational study revealed that it is feasible to retrieve a uterus safely from a LD regarding medical complications and psychosocial well beings of the donors.…”
Section: Live Donor or Deceased Donor?mentioning
confidence: 99%
“…Currently, there is no consensus on using the live donor (LD) or deceased donor (DD) for UTx, the choice is institution‐dependent and should be made based on the risk–benefit assessment from the research team (Figure ). Also, the first human uterus transplant using laparotomy or laparoscopy or robot is also based on the status of surgery and medical technology in each unit . Spanish and Japanese teams favoring the Swedish LD model, whereas teams in Turkey, Italy, France, Belgium and the UK prefer using the DD …”
Section: Live Donor or Deceased Donor?mentioning
confidence: 99%
“…Another potential area of application of robotic assistance is in uterine transplantation. Though all 12 reported cases of uterine transplantation were via the open technique, robotic assistance might find future applications in this area as well 51,52…”
Section: Robotics and Reproductive Surgerymentioning
confidence: 99%